BCL-xL is correlated with disease severity in neonatal infants with early sepsis - Wu Wenshen; Peng Qi; Huang Tianli; Liao Jinfeng; Li Ning (BMC, 2021)
Abstract Background Sepsis is the most common cause of morbidity and mortality in neonatal infants. It is essential to find an accurate and sensitive biomarker to confirm and treat neonatal sepsis in order to decrease the rate of mortality. The aim of this study was to investigate the association between disease severity in patients with sepsis and TNF-α, B cell lymphoma-extra-large (BCL-xL), and serum Mitochondrial membrane potential (MMP). Methods We investigated the correlation between SNAP-II score and levels of TNF-α, BCL-xL, and MMP-index, respectively. The receiver-operating characteristics (ROC) was to assess the diagnostic value of the the Bcl-xL in the diagnosis of the of septic shock. Results A total of 37 infants were diagnosed with sepsis. SNAP-II was positively correlated with the level of BCL-xL (r = 0.450, P = 0.006). The area under the BCL-xL curve was 83.0 %, and the 95 % CI was 67.1-93.3 %. The septic shock threshold was > 3.022 ng/mL, and the sensitivity and specificity were 75.0 and 95.2 %, respectively. The positive predictive value was 92.3 %, and the negative predictive value was 83.3 %. Furthermore, the level of SNAP-II was > 10, and BCL-xL was > 3.022 ng/mL as the threshold, and the sensitivity, specificity, positive predictive value, and negative predictive value of septic shock were 93.8 %, 95.2 %, 93.8 %, and 95.2 %, respectively. Conclusions BCL-xL is associated with the progression of sepsis. The combination of BCL-xL and SNAP-II could be early predicte the severity of the disease.